2013
DOI: 10.1121/1.4821206
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the coastal occurrence of endangered killer whales using autonomous passive acoustic recorders

Abstract: Using moored autonomous acoustic recorders to detect and record the vocalizations of social odonotocetes to determine their occurrence patterns is a non-invasive tool in the study of these species in remote locations. Acoustic recorders were deployed in seven locations on the continental shelf of the U.S. west coast from Cape Flattery, WA to Pt. Reyes, CA to detect and record endangered southern resident killer whales between January and June of 2006-2011. Detection rates of these whales were greater in 2009 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
(21 reference statements)
3
12
0
Order By: Relevance
“…5). Also, previous studies have shown that K and L pods are typically absent from their usual summertime areas during December− May (Ford 2006), and seem to make use of outer coast areas like Swiftsure (as in the present study) and waters from Washington down to California (Hanson et al 2013, Rice et al 2017. Although monitoring at all of these outer coast sites during the winter months has resulted in relatively low rates of encounter compared to summertime encounter rates in critical habitat, taken collectively this suggests that Southern Residents range widely in the winter and rely on the shelf waters of this outer coast region in its entirety in the wintertime.…”
Section: Discussionsupporting
confidence: 67%
“…5). Also, previous studies have shown that K and L pods are typically absent from their usual summertime areas during December− May (Ford 2006), and seem to make use of outer coast areas like Swiftsure (as in the present study) and waters from Washington down to California (Hanson et al 2013, Rice et al 2017. Although monitoring at all of these outer coast sites during the winter months has resulted in relatively low rates of encounter compared to summertime encounter rates in critical habitat, taken collectively this suggests that Southern Residents range widely in the winter and rely on the shelf waters of this outer coast region in its entirety in the wintertime.…”
Section: Discussionsupporting
confidence: 67%
“…Presumably, this occurred because the whales arrived after feeding on the fat rich Columbia River Chinook. SRKW were detected twice as frequently at the Columbia River in early spring than expected by chance [28]. This argument is further supported by increases in serum thyroid stimulating hormone, T4 and T3 in fasting humans and rats in response to leptin injections [20].…”
Section: Introductionmentioning
confidence: 95%
“…During our late May through October study period, the SRKWs primarily feed on Chinook salmon, increasingly dominated by Fraser River Chinook (FRC) returning to spawn in nearby rivers [28,29]. SRKWs generally spend the remainder of the year outside the Salish Sea, moving up and down the Pacific Coast, from CA to Southeast AK [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing research since 2004 has shown sufficient use of additional areas outside of Puget Sound and the Salish Sea to potentially meet the US definition of critical habitat (NOAA, 2015). The critical habitat geographic area is in review upon petition to expand the range, using acoustic (Hanson, Emmons, & Ward, 2013), satellite tagging, and prey availability data (NOAA, 2015). Previously, the spatial range of this endangered population of 74 whales was not sufficiently known, but efforts to incorporate new spatial data as well as threats (limited prey availability, anthropo-3 | TRACKING THE SPATIAL DIMENSIONS OF MARINE MAMMAL POPULATIONS from systematic census and targeted research-partly based on wellestablished data-sharing agreements between the agencies of two countries-can result in the extension of critical habitat designations to new areas.…”
Section: The Photoidentification and Acoustic Research Has Been Centrmentioning
confidence: 99%